Materials Science and Design Principles of Growth Factor Delivery Systems in Tissue Engineering and Regenerative Medicine. Issue 1 (6th November 2018) - Subbiah, Ramesh; Guldberg, Robert E.
Abstract: Growth factors (GFs) are signaling molecules that direct cell development by providing biochemical cues for stem cell proliferation, migration, and differentiation. GFs play a key role in tissue regeneration, but one major limitation of GF‐based therapies is dosage‐related adverse effects. Additionally, the clinical applications and efficacy of GFs are significantly affected by the efficiency of delivery systems and other pharmacokinetic factors. Hence, it is crucial to design delivery systems that provide optimal activity, stability, and tunable delivery for GFs. Understanding the physicochemical properties of the GFs and the biomaterials utilized for the development of biomimetic GF delivery systems is critical for GF‐based regeneration. Many different delivery systems have been developed to achieve tunable delivery kinetics for single or multiple GFs. The identification of ideal biomaterials with tunable properties for spatiotemporal delivery of GFs is still challenging. This review characterizes the types, properties, and functions of GFs, the materials science of widely used biomaterials, and various GF loading strategies to comprehensively summarize the current delivery systems for tunable spatiotemporal delivery of GFs aimed for tissue regeneration applications. This review concludes by discussing fundamental design principles for GF delivery vehicles based on the interactive physicochemical properties of the proteins and biomaterials. Abstract : Growth factor delivery is emerging as a potential alternative for healing severely injured complex tissues. Engineering delivery system with increased payloads and tunable release kinetics remains challenging in the realm of translational research. This review discusses the complexities behind growth factors and biomaterials to advance the development of modern delivery systems to meet the current challenges for effective tissue repair.